Association Between Autophagy and Neurodegenerative Diseases - Fujikake, Nobuhiro; Shin, Minkyoung; Shimizu, Shigeomi (Frontiers in Neuroscience, 2018)
Autophagy is a phylogenetically conserved mechanism that controls the degradation of subcellular constituents, including misfolded proteins and damaged organelles. The progression of many neurodegenerative diseases is thought to be driven by the aggregation of misfolded proteins; therefore, autophagic activity is thought to affect disease severity to some extent. In some neurodegenerative diseases, the suppression of autophagic activity accelerates disease progression. Given that the induction of autophagy can potentially mitigate disease severity, various autophagy-inducing compounds have been developed and their efficacy has been evaluated in several rodent models of neurodegenerative diseases.